载三氧化二砷的PEG—PLGA隐性纳米粒的制备及体外研究 - 王志清; 刘卫; 徐辉碧; 杨祥良 (中国化学工程学报（英文版）, 2007)
O6; The aim of this study was to prepare arsenic trioxide (ATO)-loaded stealth PEGylated PLGA nanoparticles (PEG-PLGA-NPs) and to assess the merits of PEG-PLGA-NPs as drug carriers for ATO delivery. PEG-PLGA copolymer was synthesized with methoxypolyethyleneglycol (Mw=5000),D,L-lactide,and glycolide by the ring-opening polymerization method. Amorphous ATO was transformed into cubic crystal form to increase its solubility in the organic solvent. ATO-loaded PEG-PLGA-NPs were prepared by the modified spontaneous emulsification solvent diffusion (SESD) method,and the main experimental factors influencing the characteristics of nanoparticles were investigated,to optimize the preparation. To confirm the escape of PEG-PLGA-NPs from phagocytosis by phagocytes,PEG-PLGA-NPs labeled rhodamine B uptake by murine peritoneal macrophages (MPM) were analyzed by flow cytometry. The results showed that the physicochemical characteristics of PEG-PLGA-NPs were affected by the type and concentration of the emulsifiers,polymer con